PS-056 Improving the culture of safety through an online incident reporting system: a national project. (24th March 2015) - De Luca, S; La Russa, R; Polidori, P; Congedo, R; Ciampalini, S; Adami, S
Abstract : Background: The project involved the Hospital Pharmacists Association network in collecting incident reports/near misses related to drugs and medical devices. There is evidence that by reporting errors and analysing error patterns there could be a reduction in medication errors (MEs). Purpose: To improve the safety culture through the development of an online national incident reporting system (IRS) in order to reduce potential MEs and increase patient safety. Material and methods: We performed a literature review of IRSs. We created our national IRS, which is available online on our Hospital Pharmacists Association national website. It is composed of three sections (context; details; causes and consequences). Submission of MEs is anonymous to guarantee confidentiality. Periodically a ME report is published on the website to educate readers in potential MEs. MEs reported between October 2011 and September 2014 were collected and analysed. We evaluated the severity of the errors reported using the American National Coordinating Council for Medication Error Reporting and Prevention Index (NCCMERPI), which classifies errors in 9 categories according to the severity of harm caused (with increasing severity from A to I). Results: From quantitative data analysis it emerged that all reports (69 valid out of 84) referred to drugs and the majority of MEs were prevented by pharmacists (50.7%). The riskiest phases turn out to be administration (52.2%), followed by prescription (29%) and distribution (8.7%). From NCCMERPI analysis it emerged that the majority of MEs reported were classified in the C category (39.1%). Conclusion: Incident reports collected suggest increasing checks (double check) throughout the medication process and developing specific checklists. We mostly need to sensitise healthcare professionals to improve incident reporting. We need to take specific initiatives on potential errors with medical devices because of the lack of reporting in this important category. References and/or acknowledgements: American National Coordinating Council for Medication Error Reporting and Prevention Index No conflict of interest.